Development and validation of the Women's Self-care Knowledge and Attitude Questionnaire (WSKAQ) - Khadijeh Khademi; Mohammad Hossein Kaveh; Abdolrahim Asadollahi; Mahin Nazari (BMC, 2024)
Abstract Background Menopausal women should learn self-care practices to enjoy a healthy lifestyle, positive health behaviors, and health status. In addition, the lack of self-care knowledge can lead to unhealthy attitudes and lifestyles, resulting in many complications. Improved self-care knowledge can foster positive attitudes, leading to healthier lifestyles as a beneficial cycle. However, menopausal women have limited knowledge about self-care and evaluation tools. Therefore, this study aimed to develop and investigate the validity and reliability of the Women's Self-care Knowledge and Attitude Questionnaire (WSKAQ) in Iranian menopausal women. Methods This cross-sectional study was conducted on 249 menopausal women, aged between 45 and 65 years and at least one year post-menopause, with a minimum literacy level of elementary education. Validation properties included construct validity, exploratory (EFA), and discriminant validity. Reliability was further established through Cronbach's α and McDonald's Omega. PASS 15 and SPSS 27 software were used to select centers, calculate sample size and analyze the data, respectively. Results The initial stage of construct validity involved the Kolmogorov-Smirnov test and EFA, resulting in a 6-item self-care knowledge subscale, 47.29% of the total data variance, and 7-item self-care attitude subscale, 55.50% of the total data variance. Independent t-test indicated that menopausal women with education level equal to or higher than diploma have significantly higher self-care attitude scores than those with lower than diploma (p = 0.007). Additionally, significant correlations were observed between self-care knowledge and attitude (r:0.30). Cronbach's α and McDonald's Omega coefficients of the 13-item WSKAQ were 0.77 and 0.78, respectively. Conclusions Based on the results, the WSKAQ, consisting of 13 items, was validated and reliable for assessing the self-care knowledge and attitude of Iranian menopausal women.